Jonas Taylor’s Leadership in The Ocean Exploration Team in The Movie Entitled Meg 2: The Trench - Yahya, Nur Afni; Laya, Rachmi; Podungge, Rusni (Pascasarjana, Universitas Negeri Gorontalo, 2024)
The object of this research is a movie entitled Meg 2: The Trench. This research aims to explain the leadership of the main character in the movie Mag 2: The Trench. This research uses a qualitative method with a sociological approach to obtain research data. This research uses leadership theory according to Bernard M Bass which will reveal Transformational leadership consisting of several leadership components and sociological theory from Swingewood which will reveal the leader's relationship with society. The results of the research based on Bernard M bass theory show that Jonas Taylor has four leadership components namely Idealized Influence, Inspirational Motivation, Intellectual stimulation, Individualized Consideration in leading exploration in the deep ocean. Then the results of research based on the sociological approach according to Swingewood's theory reveal the relationship between leaders and society. Jonas Taylor's relationship with the team and also the tourists is very well established because of the social interaction that is well built by Jonas Taylor.